Stage dreams - Gillman, Melanie (Graphic Universe, an imprint of Lerner Publishing Group, Inc., 2019)
In 1861, Grace, a runaway, and Flor, a stagecoach robber, join forces to thwart a plan by the Confederate Army in the New Mexico Territory.